Case report: Intraoperative frozen section analysis of Thyroid paraganglioma - Zhao, Huanyu; Lu, Yudie; Zheng, Jingrong; Xie, Yuyao; Li, Qingchang (Frontiers in Oncology, 2022)
Paraganglioma (PGL) is a neuroendocrine tumor that arises from the sympathetic or parasympathetic paraganglia. Primary thyroid PGL is extremely rare. PGL may be difficult to diagnose on frozen sections because its histopathological features, such as polygonal tumor cells with eosinophilic cytoplasm arranged irregularly, overlap with those of thyroid follicular adenoma. We present a case of thyroid PGL in a female patient and provide a detailed description of the patient’s clinicopathologic characteristics. Cervical computed tomography showed a left thyroid mass with uneven density. Intraoperative frozen section analysis showed an uneven fibrous septa and rich networks of delicate vessels surrounding tumor cell nests. The tumor cells were polygonal or epithelioid with eosinophilic cytoplasm, arranged in a nest, trabecular, or organoid pattern were and diagnosed as thyroid follicular adenoma. However, in postoperative immunohistochemistry, these were diagnosed as thyroid PGL. The postoperative recovery was uneventful. The patient showed no signs of tumor recurrence or metastasis until 16 months of follow-up. Herein, we summarize the characteristic features of thyroid PGL based on frozen section analysis. In the appropriate clinical context, its proper use as diagnostic and differential diagnostic management strategies is recommended.